Immature Ovarian Teratoma with Gliomatosis Peritonei- an unusual finding - Nur, Jinnatun; Akter, Sumaya; Khanom, Rashida (Journal of Dhaka Medical College, 2017)
Immature ovarian teratoma is a rarely seen germ cell tumor and Gliomatosis peritonei (GP) is a rare condition that occurs almost exclusively in the setting of ovarian immature teratoma. It is characterisized by the occurrence of nodules of mature glial tissues in the peritoneum, omentum and bowel wall. The glial tissue in such cases is usually low grade although there have been cases of malignant evolution described. In general, the prognosis for GP is good. It depends chiefly on the degree of maturity of the implants. In mature GP, usually no additional chemotherapy is necessary. In immature GP, chemotherapy can induce maturation of the implants. We present a case of immature ovarian teratoma associated with low grade GP. J Dhaka Medical College, Vol. 26, No.1, April, 2017, Page 79-82